2022
DOI: 10.21061/jvs.v8i3.324
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Veterans’ Resilience, Attachment, and Negative Affect

Abstract: On March 13, 2020, the US issued an emergency declaration in response to the COVID-19 pandemic, necessitating increased domestic engagement of the military to mount the national public health response. The US military's increased domestic health response to the COVID-19 pandemic, combined with the effects of its involvement in a 20-year war exacerbated by recent tensions around America's exit from Afghanistan, has led to increased stress on our already overburdened forces. This study compares baseline data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Researchers found that the common occurrence of generalized anxiety, depression, and PTSD is best conceptualized as the quadripartite model. 46,70,71,72 Watson 74 used a dimensional approach rather than a diagnostic classification to conceptualize the overlap between symptom presentation and the quadripartite model that is best characterized as combinations of distress and specificity. Other scholars have found that hyperarousal is consistent with high specificity and modest distress, 75 which is concerning because alternations in arousal and reactivity predicts temporal ordering of the symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers found that the common occurrence of generalized anxiety, depression, and PTSD is best conceptualized as the quadripartite model. 46,70,71,72 Watson 74 used a dimensional approach rather than a diagnostic classification to conceptualize the overlap between symptom presentation and the quadripartite model that is best characterized as combinations of distress and specificity. Other scholars have found that hyperarousal is consistent with high specificity and modest distress, 75 which is concerning because alternations in arousal and reactivity predicts temporal ordering of the symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that the common occurrence of generalized anxiety, depression, and PTSD is best conceptualized as the quadripartite model 46,70,71,72 . Watson 74 used a dimensional approach rather than a diagnostic classification to conceptualize the overlap between symptom presentation and the quadripartite model that is best characterized as combinations of distress and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Also, these participants were treatment-seeking first responders, and future work should examine nontreatment-seeking first responders. Finally, using the cutoff date of March 13, 2020, when the president issued the Proclamation on Declaring a National Emergency Concerning the Novel Coronavirus Disease-19, two studies investigated the differences between first responders (Carbajal et al, 2022) and veterans (Mallory et al, 2022) who sought treatment before and after its onset. The study of first responders found a slight decrease in resilience before and after the onset of the pandemic, but was not statistically significant (Carbajal et al, 2022) whereas the veteran sample had a slight increase in resilience, though it was not statistically significant either (Mallory et al, 2022).…”
Section: Limitations and Future Researchmentioning
confidence: 99%